Indocyanine green fluorescence for free-flap perfusion imaging revisited: advanced decision making by virtual perfusion reality in visionsense fusion imaging angiography - Bigdeli, Amir Khosrow; Henzler, Thomas (Surgical innovation, 2016)
Background. Near-infrared indocyanine green video angiography (ICG-NIR-VA) has been introduced for free-flap surgery and may provide intraoperative flap designing as well as postoperative monitoring. Nevertheless, the technique has not been established in clinical routine because of controversy over benefits. Improved technical features of the novel Visionsense ICG-NIR-VA surgery system are promising to revisit the field of application. It features a unique real-time fusion image of simultaneous NIR and white light visualization, with highlighted perfusion, including a color-coded perfusion flow scale for optimized anatomical understanding. Methods. In a feasibility study, the Visionsense ICG-NIR-VA system was applied during 10 free-flap surgeries in 8 patients at our center. Indications included anterior lateral thigh (ALT) flap (n = 4), latissimus dorsi muscle flap (n = 1), tensor fascia latae flap (n = 1), and two bilateral deep inferior epigastric artery perforator flaps (n = 4). The system was used intraoperatively and postoperatively to investigate its impact on surgical decision making and to observe perfusion patterns correlated to clinical monitoring. Results. Visionsense ICG-NIR-VA aided assessing free-flap design and perfusion patterns in all cases and correlated with clinical observations. Additional interventions were performed in 2 cases (22%). One venous anastomosis was revised, and 1 flap was redesigned. Indicated by ICG-NIR-VA, 1 ALT flap developed partial flap necrosis (11%). Conclusions. The Visionsense ICG-NIR-VA system allowed a virtual view of flap perfusion anatomy by fusion imaging in real-time. The system improved decision making for flap design and surgical decisions. Clinical and ICG-NIR-VA parameters correlated. Its future implementation may aid in improving outcomes for free-flap surgery, but additional experience is needed to define its final role.